The Principal's Leadership Role in Implementation of the Independent Curriculum in Elementary School - Fitria Desy Dwi Kisardi Putri; Honest Ummi Kalstum (Universitas Pendidikan Ganesha, 2022)
The government's policy of an independent curriculum still needs to be revised for every education staff, especially in elementary schools. Therefore it is essential that the leadership role of a school principal is to carry it out. This study aims to analyze the principal's leadership role in implementing the independent curriculum at Harjowinangun 2 Public Elementary School. This research uses a descriptive qualitative approach with a phenomenological design. Data collection techniques in this study are interviews, observation, and documentation. They are testing the validity of using triangulation techniques of data sources and methods. The data analysis used is Miles and Huberman's interactive model. The results of this study show that the principal acts as a leader in program implementation and a manager in managing and is responsible for program collaboration that will be carried out both from the learning aspect and the project to strengthen the Pancasila student profile. The principal is the most significant motivator who can influence and encourage teachers and students to improve their intellect and skills through good role models to implement the independent curriculum successfully. The implementation of the independent curriculum can be successful through the leadership and role of the principal and good cooperation with teachers and other stakeholders.